1975
DOI: 10.1159/000301518
|View full text |Cite
|
Sign up to set email alerts
|

Egg Transport in the Fallopian Tube

Abstract: The transport of eggs from the site of ovulation to the site of implantation is a fundamental step of the reproductive process in the female. The fallopian tube effects the major part of this function and times the passage of eggs into the endometrial environment. As a result of different combinations of speed of progression and retention periods through the various regions of the oviduct, the pattern of transport differs from one species to another. The roles of muscular contraction, ciliary movement and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…The cumulus cells disaggregate from one another and synthesize and secrete large amounts of a hyaluronic acid-enriched cumulus extracellular matrix (cECM), increasing the volume of the COC 20-to 40-fold [1]. This process of cumulus expansion or mucification, which occurs within the intact follicle, may be required for oocyte maturation, ovulation, and fertilization [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The cumulus cells disaggregate from one another and synthesize and secrete large amounts of a hyaluronic acid-enriched cumulus extracellular matrix (cECM), increasing the volume of the COC 20-to 40-fold [1]. This process of cumulus expansion or mucification, which occurs within the intact follicle, may be required for oocyte maturation, ovulation, and fertilization [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators ( 5 ) have suggested that a gradual increase in estradiol secretion during the final 24 hr that eggs are in the oviduct aids the passage of eggs through the uterotubal junction into the uterus. The work of Hilliard and Eaton ( 5 ) has been interpreted by some investigators to mean that tubal egg transport occurs during a period when blood levels of ovarian steroids are undetectable (7,8).…”
mentioning
confidence: 99%
“…Post-ovulatory administration of oestrogens can disturb ovum transport in several species and each one responds in a particular fashion depending on the dose and time of administration (Croxatto & Ortiz, 1975 (Ellinger & Kirton, 1974;Spilman et al, 1976;Hodgson, 1976;Takeda et al, 1977) but not in hamsters or rats (Labhsetwar, 1972(Labhsetwar, , 1973 or guinea-pigs (Maia et al, 1977). Oestradiol has been shown to be active in all species tested, producing either accelerated or delayed transport, but only a single dose was tried in the women in this study and as with the other compounds the experiment was designed to give evidence only of accelerating effects.…”
Section: Resultsmentioning
confidence: 99%